Spillover Effect of Return and Volatility Between Digital and Traditional Assets - Sadewa, Putra; Andrian, (Industrija, 2024)
This study aims to examine the spillover effects of return and volatility between  three  different  assets (Bitcoin,Gold, and Nasdaq) using  GARCH-ARMA  models. The  data  is  taken  from  monthly  closing  prices  from  January 2015  to  February  2024  through  Investing.com. The analysis  focuses  on understanding how these three assets interact regarding the spillover effect of return  and  volatility,  particularly  during  periods  of  economic  uncertainty.  Our findings  indicate  that  spillover  effects of  return are visible  from  Bitcoin  to Nasdaq, Nasdaq to Bitcoin, and Nasdaq to Gold. In addition, spillover effects of  volatility  are  visible  from  Gold  to  Bitcoin,  Bitcoin  to  Nasdaq,  Nasdaq  to Bitcoin,  and  Nasdaq  to  Gold.  Our  finding  highlights  the  dynamic  relationship between traditional and digital assets, emphasizing Bitcoin's potential role as a financial hedge likely to Gold and Nasdaq.